English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-11-14 09:23:59 · 3 answers · asked by jiles357 1 in Science & Mathematics Mathematics

3 answers

product rule:

d/dx (uv) = u'v + v'u

f'(x) = d/dx (x^2 + 1) e^x + d/dx (e^x) (x^2 + 1)

d/dx (e^x) = e^x

f'(x) = 2x (e^x) + e^x (x^2 + 1)

factor out e^x

f'(x) = e^x (x^2 + 2x + 1)

f'(x) = e^x (x+1)^2 <== answer

2007-11-14 09:28:43 · answer #1 · answered by Anonymous · 0 0

f(x)=(x^2+1)e^x
f '(x) = (x^2+1)e^x + 2xe^x = e^x(x^2+2x+1)=e^x(x+1)^2

2007-11-14 17:30:07 · answer #2 · answered by ironduke8159 7 · 0 0

I'm not sure how these other guys are getting their answers, but the answer is 2xe^x+(x^2+1)e^x.

2007-11-14 19:15:53 · answer #3 · answered by John S 2 · 0 0

fedest.com, questions and answers